The Many Functions of Foxp3+ Regulatory T Cells in the Intestine - Cosovanu, Catalina; Neumann, Christian (Frontiers in Immunology, 2020)
Throughout the last years gut-resident Foxp3+ regulatory T (Treg) cells have been associated with a growing number of tissue-specific functions in the intestine, comprising various aspects of gut immunity and physiology. Treg cells have pivotal roles in intestinal tolerance induction and host defence by actively controlling immune responses towards harmless dietary antigens and commensal microorganisms as well as towards invading pathogens. In addition to these immune-related roles, it has become increasingly clear that intestinal Treg cells also exert important non-immune functions in the gut, such as promoting local tissue repair and preserving the integrity of the epithelial barrier. Thereby, intestinal Treg cells critically contribute to the maintenance of tissue homeostasis. In order to account for this functional diversity, gut-resident Treg cells have specifically adapted to the intestinal tissue microenvironment. In this Review, we discuss the specialization of Treg cells in the intestine. We survey the different populations of gut-resident Treg cells focussing on their unique functions, phenotypes and distinct transcription factor dependencies.